Household formation and residential energy demand: Evidence from Japan - Carsten Schröder; Katrin Rehdanz; Daiju Narita; Toshihiro Okubo (Kiel Institute for the World Economy (IfW), 2013)
We use a large household panel for Japan (Keio Household Panel Survey) to estimate household-size economies in energy consumption. The household-size economies we obtain are significant and sizable: the per-capita energy-related spending of a two-adult household is only about two-thirds of the expenditure of a one-adult household. We use the estimates of household-size economies to explore how the demographic trend toward smaller-sized household units changes energy demand in the Japanese household sector. Between 2005 and 2010, for example, average household size in Japan decreased by about five percent. The resulting economy-wide loss in household-size economies increased energy demand in the household sector by about four percent.
Keywords: 330; energy consumption; household-size economies; demographic change; household formation